(untitled) (Materiali di Estetica. Terza serie, 2025)
Animalistic art not only denounces the terrible situation in which animals live due to anthropocentrism. It also aims to become a pedagogy of empathic care that can transform our consciousness and make social and political change possible. To this end, it cannot limit itself to being an aesthetic theory of care but must itself be caring and empathetic towards animals. Nevertheless, there has been animalistic art that has subordinated the ethics of care to purely artistic achievements. In contrast, in this paper we defend an animalistic art that is inseparable from the animalistic ethic of care. Only this art can be a true pedagogy of empathic care for animals.